The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s41598-022-19376-1
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and its correlates among Bangladeshi older adults during the COVID-19 pandemic

Abstract: The present study aims to investigate the prevalence of loneliness and its associated factors among older adults during the COVID-19 pandemic in Bangladesh. This cross-sectional study was conducted in October 2020 among 1032 older Bangladeshi adults aged 60 years and above through telephone interviews. A semi-structured questionnaire was used to collect information on participants’ characteristics and COVID-19-related information. Meanwhile, the level of loneliness was measured using a 3-item UCLA Loneliness s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Nine studies indicated that the prevalence of Si/L was less common in rural areas, compared to urban areas, with a primary focus on loneliness. These studies were conducted in five different countries, including Bangladesh [ 41 , 42 ], Canada [ 43 , 44 ], France [ 45 ], Serbia [ 46 ], the United States (US) [ 47 ], and the United Kingdom (UK) [ 48 , 49 ]. Several studies determined rural areas to be a protective factor against Si/L, and identified women, those with financial challenges and additional chronic health issues, as groups with the highest prevalence or risk of loneliness [ 47 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine studies indicated that the prevalence of Si/L was less common in rural areas, compared to urban areas, with a primary focus on loneliness. These studies were conducted in five different countries, including Bangladesh [ 41 , 42 ], Canada [ 43 , 44 ], France [ 45 ], Serbia [ 46 ], the United States (US) [ 47 ], and the United Kingdom (UK) [ 48 , 49 ]. Several studies determined rural areas to be a protective factor against Si/L, and identified women, those with financial challenges and additional chronic health issues, as groups with the highest prevalence or risk of loneliness [ 47 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study by Mistry et al (2022a) conducted two periods of data collection in 2020 and 2021. In this study, the prevalence of loneliness was found to have dropped significantly from 2020 to 2021, which suggests some adaptation to the pandemic occurred in older, rural dwelling Bangladeshi adults [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Despite the importance of social connections in effectively protecting and promoting mental health, 51 the lack of social interaction and family visits due to the lockdowns and social restrictions posed by the Government of Bangladesh to curve the spread out of coronavirus impacted mental health, especially of the older population. 17,52,53 As social isolation increases, feelings of loneliness also increase, 54 which is strongly linked to depression. 46 The presence of chronic conditions was associated (aOR: 1.34, 95% CI 1.06-1.69) with higher depression among our study participants.…”
Section: Discussionmentioning
confidence: 99%
“…The participants were classified as lonely if they answered ‘some of the time’ or ‘often’ to any item [ 42 ]. The scale was previously used among Bangladeshi population [ 43 ].…”
Section: Methodsmentioning
confidence: 99%